Ambientes deposicionais e evoluÇÃo estratigrÁfica do cretÁceo superior da bacia dos parecis - Batezelli, Alessandro; Sergio Bernardes Ladeira, Francisco; Assine, Mario Luis [UNESP] (My University, 2014)
Although there are many publications about the Brazilian Cretaceous basins, the understanding of tectonic and climatic processes concerned in the evolution of continental sequences still needs studies, especially those related to central-western portion. The Upper Cretaceous sedimentary sequence of the Parecis Basin, lies unconformably on volcanic rocks of the Anari and Tapirapuã formations (Lower Jurassic) and Lower Cretaceous Rio Ávila Formation sandstones. This unit consists of alluvial conglomerates and sandstones at the base (Salto das Nuvens Formation) and aeolian sandstones on the top (Utiariti Formation). From facies analysis and stratigraphic architecture a paleoenvironmental model was prepared, including tectonic and climatic evolution during the Late Cretaceous. Using the concept of stratigraphic base level and/or the ratio of accommodation space and sediment supply (A/S), was identified the stacking pattern of alluvial and aeolian, corresponding to different stages of Juruá Tectonic. The events of sedimentation began after the genesis of a regional unconformity (unconformity K-1) between the Early and Late Cretaceous. During the Late Cretaceous the Parecis Basin took an alluvial sedimentation cycle (Sequence 1A) followed by aeolian cycle (Sequence 1B). The first stage records an increase in the A/S ratio where it developed alluvial fans reworked by braided rivers and aeolian process (High Accommodation System Tract-HST). Progressively the accommodation space was decreasing, and draas landforms was developed (Low accommodation System Tract-LST). In the final stage the A/S has become negative and unconformity K-2 was made. The facies from the base to the top mark the climate evolution in the basin, from humid to the dry. Paleocurrent data indicate that the souce area was the Tapajós High in the north of the basin.
Keywords: Accommodation space; Aeolian facies; Alluvial facies; Parecis Basin; Sediment supply; Stratigraphic sequence